KAJIAN PENGGUNAAN OBAT ANTIHIPERTENSI PADA PASIEN DIABETES MELITUS TIPE 2 DI INSTALASI RAWAT INAP BLU RSUP PROF. DR. R. D. KANDOU MANADO PERIODE JANUARI-DESEMBER 2010 - Ansa, Dian; Goenawi, Lily; Tjitrosantoso, Heedy (UNIVERSITAS SAM RATULANGI, 2012)
Hypertension in patient with type 2 diabetes mellitus (DM type 2) improve microvascular andmacrovascular complications. Control of blood pressure can reduce the risk of complication andmortality. The aims of the study was to assess antihypertensive in patients with type 2 diabetes atBLU. RSUP. Prof. Dr. R. D. Kandou Manado, from January to December 2010. This study was aretrospective descriptive study. The data was collected by purposive at the installation of medicalrecords BLU. RSUP. Prof. Dr. R. D. Kandou Manado, from October to December 2011, and a total of41 diabetic patients involve in this study. The findings of ths study showed that the majority patientstype 2 diabetes in the age range between 45 to 64 years (70,73%). Patterns of antihypertensivetherapy consists of monotherapy (53,66%) and combination (46,34%). In the monotherapy, which isoften used Angiotensin Converting Inhibitors (ACE-I) (31,82%), Calcium Channel Blockers (CCB)(27,27%), and Angiotensin Receptor Blocker (ARB) (22,73%). For the combination therapy group,which is often used combination of ACE-I and CCB, ARB and CCB each one(21,05%), andcombination ACE-I and ARB (15,83%).Key words: hypertension, type 2 diabetes mellitus, hypertension treatment.